IMPACT OF INDIVIDUAL CHANGE READINESS AND SAFETY PERFORMANCE ON PROJECT SUCCESS: ROLE OF PROJECT MANAGER RELATED FACTORS AND PROJECT COMPLETION TIME - Musaddag Elrayah; Sanjar Mirzaliev (Operational Research in Engineering Sciences: Theory and Applications)
This study examines the impact of individual change readiness on project success, emphasizing the mediating role of strategies to improve safety performance and the moderating role of project manager-related factors. Additionally, it compares these relationships in short-term and long-term projects to assess variations based on project duration. A quantitative research approach was employed, collecting data from 243 project professionals, with 120 respondents from long-term projects and 123 from short-term projects. The sample included project managers, team leaders, and safety officers involved in project execution. Structural Equation Modeling (SEM) using Smart-PLS was applied to assess measurement validity, test hypothesized relationships, and conduct multi-group analysis (MGA) for comparative insights. The results confirm that individual change readiness significantly enhances project success, with strategies to improve safety performance serving as a crucial mediator. Additionally, project manager-related factors moderate the relationship between change readiness and project success. The influence of these variables differs between short-term and long-term projects, emphasizing the contextual nature of project management. This study contributes to the project management literature by integrating change readiness and safety strategies into a unified framework. It offers practical insights for organizations to optimize project success through effective leadership, change management, and safety practices tailored to project duration.